Printed 3D Gesture Recognition Thermoformed Half Sphere Compatible with In‐Mold Electronic Applications - Gomes Correia, Vítor Manuel; Pereira, Nelson; Perinka, Nicola; Costa, Pedro; del Campo, Javier; Lanceros-Mendez, Senentxu (Advanced engineering materials, 2022)
The development of conformable electronic systems’ focuses on the multifunctional smart materials transform areas from the automotive industry to biomedicine, based on improved integration and advanced functionalities. In‐mold electronics (IME) combines thermoforming, injection molding, and printed electronics, resulting in sensing structural parts integrated into smart surfaces, communicating with computer systems, and enabling advanced experiences in terms of human‐machine interaction. Contrary to flexible electronics, designed as bend conductors around a single axis, thermoformed electronics allow deformations in the three‐axial directions for different geometries. Herein, a 2D screen‐printed pattern using conductive silver ink thermoformed into a spherical surface suitable for 3D gesture recognition is reported. The mechanical deformation of the high‐impact polystyrene sheet (HIPS) and polyethylene terephthalate‐glycol (PETG) substrates during the thermoforming process of the electrical circuit is characterized experimentally. The electrical resistance changes through the circuit in the stages of the fabrication process due the thickness decrease and the propagation of the small cracks. Both evaluations contribute to a better understanding of the performance of the materials when subject to the IME process. Validation of the 3D gesture recognition operation is carried out, demonstrating their full operability, as well as the possibilities that the combination of technologies allows. A 2D screen‐printed pattern using conductive silver ink is thermoformed into a spherical surface geometry suitable for 3D gesture recognition. Two different polymer substrates, high impact polystyrene sheets (HIPS) and polyethylene terephthalate glycol (PETG), are thermoformed and the processed electrical circuit is characterized theoretically and experimentally, demonstrating the suitability of the system for 3D gesture recognition with a human hand.